Shaping Quality Islamic Education in the Digital Age - Tugiah; Jon Syahputra; Islahati; Demina; Zulmuqim (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This study aimed to analyze the quality of Islamic education in the face of the digital era. This research uses qualitative research with a descriptive analysis approach. The data used in this research is secondary data collected through the literature study method. The results of this study indicate that learning Islamic religious education in schools to form children's character will be better if it arises from spiritual awareness reflected in all the behaviour of the nation's life. Religious behaviour will be able to grow and develop if Islamic education is integrated with all subjects, as well as science and technology. The combination of Islamic religious education with science and technology is necessary because religion is tasked with guarding and controlling the negative impacts of technology itself.